Pengaruh Kualitas Produk, Harga, dan Citra Merek pada Keputusan Pembelian Mobil - Widiastuti Alawiah; Andyan Pradipta Utama (Universitas Prasetiya Mulya, 2023)
This study ains to analyze the influence of product quality, price and brand image on purchasing decisions for Toyota Calya Car at DKI Jakarta. The approach used in this research is survey research because it takes a sample from one population and take a sample size of 220 respondens with purposive sampling. The Methods of data collection using survey method, with the research instrument is a questionnaire. The data analysis method using Partial Least Square. This study proves that product quality has a positif and significant impact on purchasing decisions, the price has a positif and significant impact on purchasing decisions and brand image has a postif and significant impact on purchasing decisions.